CP-050 Posaconazole and invasive fungal infection. (24th March 2015) - Clara, M; Daniel, B; Susana, M; María Belén, M; Cristina, B; Lydia, R; Luis, B; Concepción, D
Abstract : Background: Invasive fungal infection (IFI) is a serious problem due to its high incidence, morbidity, mortality and budget impact. Therefore strategies are needed for antifungal use optimisation. Posaconazole has the approval of our Hospital Pharmacy and Therapeutics Committee (PTC) for its use in IFI prophylaxis in patients diagnosed with acute myeloid leukaemia (AML), myelodysplastic syndrome, oropharyngeal candidiasis, and in treatment of refractory cases of IFI. Purpose: To analyse posaconazole use, assessing the compliance with the criteria established by our PTC, and also its efficacy, safety and budget impact. Material and methods: We have carried out a retrospective study of patients under posaconazole treatment in our hospital between September 2013 and September 2014. We gathered data from patients' clinical history and the Farmatools unit dose records module about age, gender, diagnosis, indication, posology, treatment length, previous treatment lines, clinical analytics and microbiology, outcomes, adverse events, drug interactions and laboratory selling price. Results: We found data from eleven patients (81% male, average age 52 years, 18 minimum and 86 maximum). Average posaconazole dose was 600 mg/day, and average treatment length was 12.8 days. The most frequent diagnosis was AML (4), followed by myelodysplastic syndrome (3), current IFI (2), iatrogenic agranulocytosis (1) and aplastic anaemia (1). In most cases (90.9%) posaconazole use met PTC criteria; the remaining indications weren't approved (first line treatment for current IFI). The outcome was positive for 81.8% of patients, the remaining two switched to another antifungal because of symptoms suggestive of IFI. All experienced increases in transaminases and direct bilirubin, improving after treatment ended. Main drug interactions involved ranitidine and ciclosporin. Total cost was € 33, 899.47 (average per patient €3000). Conclusion: PTC criteria were met in most of the cases, but posaconazole use for non-approved indications represented an additional cost of €18, 155.4, which emphasises the need for tight control of criteria compliance. References and/or Acknowledgements: No conflict of interest.